Disentangling the pattern of geographic concentration in Tunisian manufacturing industries - Mohamed Ayadi; Wided Mattoussi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
In this paper, we examine the pattern of spatial concentration of manufacturing industries observed in Tunisia and explore the factors driving firms' choices of location at the provincial level. We consider specialization and competition indicators as the driving forces and also examine the extent to which location choice is related to centre business districts. We estimate the effect of the location variables on sector growth and productivity. Our results suggest that firms choose to locate in a specific governorate because of high local demand, which brings about transportation cost savings. Moreover, we find a concentration of activity in Greater Tunis where most growth in firms and employment are observed, while locating in littoral governorates enhances the productivity growth of governorate industries.
Keywords: D22; L25; R12; R32; 330; industrial concentration; concentration index; competition index; Tunisia